X-rays microdetectors based on an array of scintillators: a maskless process using laser ablation - Rocha, J. G. (2002)
This paper describes a X-rays microdetector based on an array of wells filled with scintillator crystals. A thick-film of aluminum (500 um) is etched by Laser Ablation Technique (LAT) in order to achieve a square well with side of 100 um and 490 um deep vertical sidewalls. The aluminum thick-film was chosen because it is a good reflector in the visible range and for improving the number of photons collected by each photodetector. Also, the cross-talk between adjacent wells is reduced. As first approach, for a 4x4 wells array prototype, LAT is an inexpensive process when compared with Deep Reactive Ion Etching (DRIE) and avoids the need of etching masks. In this system the X-ray energy is first converted to visible light by the scintillator. This light is then detected by a photodetector fabricated in a standard CMOS process.